MARKETING STRATEGY ANALYSIS USING THE SWOT APPROACH AT PT SERENA INDOPANGAN INDUSTRI - Eidelweijs Adririnjani Putri; Mujito Mujito; Tika Kartika Asri; Andri Catur Trissetianto (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze and formulate appropriate marketing strategies for PT Serena Indopangan using a SWOT (Strengths, Weakness, Opportunities, and Threats) analysis approach. The research employs a descriptive qualitative method, with data collected through observations, interviews, and documentation. The results indicate that the company’s strengths lie in its product quality and extensive distribution network, while its weaknesses include limited digital marketing activities and lack of product innovation. On the external side, growing market demand and changes in consumer lifestyles present significant opportunities, whereas intense competition and fluctuating raw material prices pose major threats. Based on the SWOT analysis, the most suitable strategy for PT Serena Indopangan is the SO (Strengths-Opportunities) strategy, which focus on leveraging internal strengths to capitalize on external opportunities. The study recommends enhancing digital marketing efforts and strengthening brand positioning to improve the company’s competitiveness.